Analysis of the Influence of Digital Comment History on The Effectiveness of Product Sales Strategies in E-Commerce Shopee - Seniorita; Febri Sari Siahaan; Mahrizal; Amat Suroso; Lilik Suryaningsih (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to analyze how the influence of digital comment factors affects the level of product sales on Shopee e-commerce. We use a quantitative-qualitative approach, utilizing primary data from digital product sales, opinions, and consumer assessments in e-commerce, along with secondary data from sources like product-related literature. The study population includes all products available through e-commerce. The sampling technique uses a combination of probability sampling and non-probability sampling. The research results show that the digital comment variable has a significant influence on the level of product sales in e-commerce. Research demonstrates that positive opinions significantly boost product sales, aligning with the widely held belief that positive feedback can bolster consumer interest and confidence in the product. On the other hand, negative opinions also show a significant positive influence, indicating that transparency and honesty in consumer reviews can have a beneficial impact on product sales. This highlights the importance of not only focusing on positive feedback but also managing negative reviews well as part of an effective marketing strategy in digital environments such as e-commerce. Digital consumer assessments do not show a significant influence on product sales. This suggests that consumers tend to trust first-hand experiences from other consumers' reviews rather than relying solely on numerical ratings in isolation.